2003
DOI: 10.1124/jpet.103.053199
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase Is the Major Enzyme Metabolizing Buprenorphine in Human Placenta

Abstract: Buprenorphine (BUP) is a partial opiate agonist used for treatment of the adult and the pregnant addicted to this class of narcotics. The kinetic parameters for transplacental transfer and the metabolism of BUP during its perfusion in a placental lobule were the subject of an earlier report from our laboratory. The aim of this investigation is to identify and characterize the enzyme catalyzing the metabolism of BUP in term human placenta. Norbuprenorphine (norBUP) is the only metabolite formed as determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 30 publications
3
26
0
1
Order By: Relevance
“…Accordingly, placental disposition of methadone would be achieved by its metabolism of the drug or its efflux back to the maternal circulation. Earlier reports from our laboratory provided evidence supporting our working hypothesis by identifying aromatase/CYP 19 as the major enzyme responsible for the metabolism of the opiates BUP to norBUP [27], LAAM to norLAAM [28], and methadone to EDDP [5]. It is interesting to note that the major enzyme responsible for the metabolism of these opiates in human liver and intestine is CYP 3A4 [29][30][31].…”
Section: Discussionsupporting
confidence: 72%
“…Accordingly, placental disposition of methadone would be achieved by its metabolism of the drug or its efflux back to the maternal circulation. Earlier reports from our laboratory provided evidence supporting our working hypothesis by identifying aromatase/CYP 19 as the major enzyme responsible for the metabolism of the opiates BUP to norBUP [27], LAAM to norLAAM [28], and methadone to EDDP [5]. It is interesting to note that the major enzyme responsible for the metabolism of these opiates in human liver and intestine is CYP 3A4 [29][30][31].…”
Section: Discussionsupporting
confidence: 72%
“…Some data suggest that the placental transfer of this opioid may be limited in comparison with others, such as methadone, thereby limiting fetal exposure and the development of dependency. 126 Deshmukh and colleagues 127 have demonstrated that a large proportion of buprenorphine is metabolized to Norbuprenorphine, the only metabolite formed as determined by high-performance liquid chromatography and mass spectrometry, by placental aromatase (CYP 19) within the microsomal fraction of the trophoblast.…”
Section: Opiate Addictionsmentioning
confidence: 99%
“…Aromatase has been implicated in the metabolism and, specifically, the demethylation of a number of drugs in vitro, including methadone, 18 buprenorphine, 31 and cocaine, 32 but the role that this enzyme plays in the metabolism of xenobiotic medications in humans has not been directly examined before in a clinical study. The clinical trial reported here examined the Data are presented as mean T SD (n = 15).…”
Section: Discussionmentioning
confidence: 99%